2022
DOI: 10.1155/2022/2802892
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review with Meta-Analysis of Comparative Efficacy and Safety of Risankizumab and Ustekinumab for Psoriasis Treatment

Abstract: Biological targeted therapy serves as a new alternative treatment for psoriasis due to its minimal side effects. This study is aimed at examining the drug effectiveness and safety of risankizumab and ustekinumab for psoriasis treatment, so as to provide a reference for clinical decision-making. Databases from Embase, Web of Science, PubMed, and Cochrane Library were gathered, starting from inception to March 1, 2022, for randomized controlled trials regarding risankizumab and ustekinumab for psoriasis treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We identified 28 MAs/NMAs published between January 2021 and May 2023, investigating and comparing the effect of systemic therapies for moderate-to-severe adult plaque psoriasis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A total of 10 analyses were excluded for the following reasons: insufficient information on the compared therapies in the abstract, the absence of the full text [ 28 , 29 , 30 ], the full text being in a language other than English [ 31 ], being a comparison to a placebo [ 32 , 33 , 34 , 35 , 36 ], or the absence of a direct comparison between therapies [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 28 MAs/NMAs published between January 2021 and May 2023, investigating and comparing the effect of systemic therapies for moderate-to-severe adult plaque psoriasis [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A total of 10 analyses were excluded for the following reasons: insufficient information on the compared therapies in the abstract, the absence of the full text [ 28 , 29 , 30 ], the full text being in a language other than English [ 31 ], being a comparison to a placebo [ 32 , 33 , 34 , 35 , 36 ], or the absence of a direct comparison between therapies [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The safety of the molecules was compared in two MAs [ 13 , 23 ] and two NMAs [ 18 , 21 ]. Although one meta-analysis indicated that risankizumab was better tolerated than infliximab, ChatGPT’s output was rated as different, as the AI estimated that these two drugs had a similar safety profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FDA approval is indicated for use in moderate to severe plaque psoriasis (Ps) for patients 6 years of age and older. 48 , 49 Main articles regarding the use of ustekinumab for the management of hidradenitis suppurativa in real-life setting are reported in Table 2 .…”
Section: Ustekinumabmentioning
confidence: 99%
“…The second generation of selective anti-IL-23 therapies targets IL-23p19, and they have demonstrated greater effectiveness compared to ustekinumab in treating other immune-mediated conditions, such as plaque psoriasis, prompting us to explore their potential use in IBD [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%